Xác định thành phần của phức chất triphenylphosphin oxit-ytri từ môi trường axit nitric - Đại, Lưu Minh; Nhiệm, Đào Ngọc (Vietnam Journal of Chemistry, 2014)
The study on solvent extraction of rare earth elements such as Nd, Y from nitric acid solutions with triphenylphosphin oxide (TPPO) has been studied. The influence of various factors such as concentrations of Triphenylphosphin oxide, nitric acids and rare earth elements on the distribution coefficient has been studied. The formulation of extracted complex has also been presented by using the method of ICP analysis [2].